Deposition and preservation of tephra in marine sediments at the active Hikurangi subduction margin. (1st November 2020) - Hopkins, Jenni L.; Wysoczanski, Richard J.; Orpin, Alan R.; Howarth, Jamie D.; Strachan, Lorna J.; Lunenburg, Ryan; McKeown, Monique; Ganguly, Aratrika; Twort, Emily; Camp, Sian
Abstract: Tephra (volcanic ash) deposits are important isochronous markers for correlating marine sediments or events recorded in marine sediment cores. However, the active tectonics that are commonly associated with volcanic activity at plate tectonicboundaries also drive large-scale deformation, leading to steep and variable local and regional bathymetry (e.g., ridges, basins and canyons systems). This complex bathymetry influences gravity-flow behaviour and paths, which can rework and redeposit tephras, resulting in stratigraphic complexities. Such as, the mis-identification of primary versus reworked tephra deposits, and in turn lead to the development of inaccurate chronostratigraphies. Here we present 36 tephra deposits from 21 shallow marine sediment cores that traverse the length of the southern and central margin of eastern North Island, New Zealand. Using major and trace element geochemical compositions for glass shards from the tephras, we correlate these deposits to three major rhyolitic eruptions from the Taupō Volcanic Zone (TVZ) approximately 200 km west, including; Taupō (1718 cal yrs. BP), Kaharoa (636 cal yrs. BP), and Kawakawa/Oruanui (KOT; 25.4 ka). Based on their morphology, depositional character and inferred emplacement mechanisms, the tephra deposits are grouped into four lithofacies types; (1) primary deposits, (2) volcaniclastic-rich turbidites, (3) blebs/pods of volcaniclastic-rich material, and (4) complex deposits. Primary deposits form syn-eruptively through airfall onto the ocean surface, settling over hours to days through the water column under diffuse vertical gravity currents. Volcaniclastic-rich turbidites are formed through secondary redeposition and entrainment by post-eruptive turbidity currents, while blebs/pods of material are interpreted to have formed by erosion and/or bioturbation. Complex deposits form through the interaction of all these mechanisms producing an overthickened array of primary and redeposited units within a single facies. Herein, we argue that redeposited units of volcaniclastic-rich turbidites or small blebs/pods can be used as tentative chronological markers if the geochemical composition of the glass shards have a homogeneous signature, i.e. a single eruptive source. Where the glass shards in redeposited units have mixed geochemical compositions, and are not stratigraphically associated with a primary deposit source, they cannot be used as chronological marker horizons. This emphasises the need for accurate and rigorous data reduction without overlooking the importance of data points that are statistical outliers. We also show that the highest preservation of tephra deposits is found in semi-confined isolated basin settings, including a wide range of deposit types. Due to erosive sediment flows that bypass through submarine distributary systems, these major sediment dispersal pathways preserve few volcaniclastic deposits. Our findings have important implications not only for identifying primary or redeposited characteristics in marine tephras for building accurate chronostratigraphies, but also as a guide geomorphic sub-environments with the best preservation of tephras in marine sedimentary systems. Highlights: Sedimentary characteristics and geochemistry of tephra deposits are reported across 21 cores. Four types of tephra lithofacies are distinguished. Geomorphic sub-environments play a key role in tephra preservation. Isolated semi-confined basin settings generally preserve the highest number of tephra deposits. For eruptions VEI≥6 volcaniclastic sediments may swamp the marine system for centuries.